Plan urbano en la gestión pública de los Gobiernos locales del Perú - Soto-Velásquez, María Elena (2023)
Objective: To demonstrate that the urban plan contributes to the public management of local governments in Peru. Method: The research was developed with a qualitative approach, documentary review, descriptive phase, cross-sectional and non-experimental procedure; the documentary review began with the data collection and continued with the review and analysis of the information, without failing to evaluate the context. Results: The Ministry of Housing, Construction and Sanitation (MVCS) indicates that the percentage of public investment in urban development at the national level in 2021 was very low, so this figure did not reach the projected target, and was even lower than the percentage reached in 2020. These results confirm the inefficiency of local governments' public management in relation to the elaboration of urban plans. Conclusion: Finally, urban plans are fundamental technical instruments in the organization of cities, and without them, it will not be possible to achieve the sustainable urban development that is essential to improve the population’s quality of life.